A hidden burden of neonatal illness? A cross-sectional study of all admissions aged less than one month across twelve Kenyan County hospitals - Murphy, Georgina A.V. (Wellcome Open Res, 2018)
Background: Small and sick newborns need high quality specialised care within health facilities to address persistently high neonatal mortality in low-income settings, including Kenya. Methods: We examined neonatal admissions in 12 public-sector County (formerly District) hospitals in Kenya between November 2014 and November 2016. Using data abstracted from newborn unit (NBU) admission registers and paediatric ward (PW) medical records, we explore the magnitude and distribution of admissions. In addition, interviews with senior staff were conducted to understand admission policies for neonates in these facilities. Results: Of the total 80,666 paediatric admissions, 28,884 (35.8%) were aged ≤28 days old. 24,212 (83.8%) of neonates were admitted to organisationally distinct NBUs and 4,672 (16.2%) to general PWs, though the proportion admitted to NBUs varied substantially (range 59.9-99.0%) across hospitals, reflecting widely varying infrastructure and policies. Neonatal mortality was high in NBUs (12%) and PWs (11%), though varied widely across facilities, with documentation of outcomes poor for the NBUs. Conclusion: Improving quality of care on NBUs would affect almost a third of paediatric admissions in Kenya. However, comprehensive policies and strategies are needed to ensure sick neonates on general PWs also receive appropriate care.